Multi-Target Molecular Docking of Anantmul (Hemidesmus indicus) Compounds for Tay-Sachs Disease Treatment - Suhas Sreehari (International Journal of Bioinformatics and Computational Biology, 2024)
This research aimed to study the effects of the plant Anantmul (Hemidesmus indicus) in the treatment of Tay-Sachs disease using molecular docking studies. Tay-Sachs disease is a neurodegenerative autosomal recessive disorder caused due to accumulation of the molecule GM2 ganglioside which is caused due to lack of enzyme Beta Hexosaminidase which breaks down GM2 Ganglioside. Anantmul (Hemidesmus indicus) is a an ayurvedic plant used in the Indian subcontinent that has many medicinal uses, such as anti-cancer, anti-diabetic, anti-inflammatory, etc. using IMPATT software about 110 phytochemicals were discovered in Anantmul, then using SWISS Absorption, Distribution, Metabolism, and Excretion about 45 compounds were screened based on the Lipinski’s rule. Then they were further screened based on toxicity using ProTox software down to 11 compounds. These 11 compounds were selected for molecular docking analysis on the protein Hexosaminidase to study their interaction and binding energy. Out of these, the top 6 compounds with the highest binding energy were taken for visualization. The compound with the highest binding energy was found to be Abieta-7,13-dien-18-oic acid with a binding energy of –7.4.
Keywords: GM2 ganglioside; Lipinski’s rule; Tay-Sachs disease; beta-hexosaminidase; molecular docking